INTENSITY OF ACCUMULATION OF HEAVY METALS AND TRACE ELEMENTS IN THE VEGETATIVE MASS OF COTTON GROWN ON GREY FOREST SOILS OF THE RIGHT-BANK FOREST-STEPPE - Razanov , С.; Alieksieiev , О.; Razanova , А.; Bakhmat , О.; Datsko , Т.; Dydiv , А. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The intensification of crop production leads to an increase in production volumes, which in turn raises the technogenic burden on the environment, particularly concerning soil quality and safety of crop products. A significant environmental threat is the accumulation of heavy metals, whose presence in soils has increased significantly due to the extensive use of mineral fertilizers, pesticides, industrial emissions, and the ongoing military aggression of russia against Ukraine. This article explores the accumulation of heavy metals (lead and cadmium) and trace elements (zinc and copper) in the vegetative mass of cotton (Gossypium L.) cultivated on the grey forest soils of the Right-Bank Forest-Steppe. The study involves an analysis of the concentrations of these elements in both soil and plant biomass, as well as determining accumulation coefficients of heavy metals to evaluate the efficacy of the Dniprovskyi 5 cotton variety for phytoremediation in contaminated areas. The findings indicate that zinc is the most readily accumulated element within the cotton's vegetative mass, occurring nearly four times more than copper and eight times more than lead. Copper ranks second in terms of accumulation, being 2.2 times more than lead and 21 times more than cadmium. Notably, the concentration of cadmium in the vegetative mass is the lowest among all the heavy metals studied. In terms of accumulation levels in the aboveground parts of the cotton plant, the order of heavy metals and trace elements is arranged from lowest to highest as follows: cadmium → lead → copper → zinc. Based on the accumulation coefficient (Ca), cotton has been found to have a high capacity for accumulating copper (Ca = 45.9) and zinc (Ca = 19.4), indicating its effectiveness in phytoremediation of contaminated areas. The accumulation of lead (Ca = 3.73) and cadmium (Ca = 4.57) in the vegetative mass also confirms the plant’s ability to extract toxicants from the soil. The potential of using cotton plants for soil remediation from heavy metal contamination has been assessed. The obtained results can be used for developing phytoremediation strategies and evaluating the environmental safety of agroecosystems.